2018
DOI: 10.1111/cmi.12959
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysin Sph2 of Leptospira interrogans induces cell apoptosis via intracellular reactive oxygen species elevation and mitochondrial membrane injury

Abstract: Leptospira interrogans causes widespread leptospirosis in humans and animals, with major symptoms of jaundice and haemorrhage. Sph2, a member of the sphingomyelinase haemolysins, is an important virulence factor for leptospire. In this study, the function and mechanism of Sph2 in the pathogenesis of leptospirosis were investigated to further understand the pathogenesis of leptospire. Real-time PCR analysis of expression levels during cell invasion showed that sph2 gene expression was transiently induced in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The apoptosis inductivity of pathogenic Leptospira has been found to be associated with virulence proteins. Recently, several studies reported the role of the Fas-binding outer membrane protein and recombinant hemolysin (Sph2) of L. interrogans in the induction of apoptosis in macrophage, umbilical vein endothelium, embryo liver, and human lung epithelial cells [29][30][31]. Here, we demonstrated that Vero cells exposed to 100 µM peptide for 24 h developed late apoptosis.…”
Section: Discussionmentioning
confidence: 66%
“…The apoptosis inductivity of pathogenic Leptospira has been found to be associated with virulence proteins. Recently, several studies reported the role of the Fas-binding outer membrane protein and recombinant hemolysin (Sph2) of L. interrogans in the induction of apoptosis in macrophage, umbilical vein endothelium, embryo liver, and human lung epithelial cells [29][30][31]. Here, we demonstrated that Vero cells exposed to 100 µM peptide for 24 h developed late apoptosis.…”
Section: Discussionmentioning
confidence: 66%
“…Mce binds to the α5β1 and αVβ3 integrins and mediates the Leptospira internalization into macrophages ( 81 ). Pathogenic Leptospira (LIC, LA, and LIHH) genome consists of five sphingomyelinase genes ( sph-1 to sph-4 , as well as sphH ), out of which sph-2 is reported to be most secreted during infection and is involved in mediating the invasion of bacteria in lung and liver cells through clathrin-mediated endocytosis, thereby inducing apoptosis ( 33 , 35 , 87 , 88 ). Next, in our conjoint analysis, we found that 19 proteins predicted to be secretory are upregulated ( Table 1 ; see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most deaths from leptospirosis are attributed to renal failure and/or gastrointestinal, pulmonary, or cerebral hemorrhage ( 24 26 ) caused by extensive capillary damage including extensive renal necrosis and glomerular atrophy. Some bacterial pathogens produce hemolysins including Sph2, and the expression of Sph2 is highest among epithelial cells ( 27 ). L. interrogans Sph2 was recently found to trigger inflammatory reaction, cytomembranous injury, and apoptosis by damaging the membranes of blood vessel endothelial cells through increasing intracellular reactive oxygen species (ROS) and decreasing the mitochondrial membrane potential (MMP).…”
Section: Discussionmentioning
confidence: 99%